Senyawa polisiklik aromatik hidrokarbon (PAH) dalam air laut di Teluk Jakarta - Edward . (Depik, 2014)
Research on polycyclic aromatic hydrocarbons (pah)s compound at Jakarta Bay seawater were carried out on July 2011. The objectives of this research were to measure the concentration of total polycyclic aromatic hydrocarbons (PAH) compound, concentration of individual PAH compound, and to identify sources of PAH compound in seawater. PAH compound concentration was measured by Gas Chromatography (Gas Chromatography-Flame Ionization Detector) and sources of polycyclic aromatic hydrocarbons compound were identified by diagnostic ratio analysis. The results show that the concentration of PAH compound in the middle of Jakarta Bay was higher compared to the west and the east. In the west and middle of Jakarta Bay, it is found that 11 PAH types, and 10 types in the east. Individual PAH compound dominated by high moleculer weight of PAH Benzo(a)Anthracene, Chrysene, Benzo(b)Fluoranthene, Benzo(a)Pyrene, dan Indeno(123-cd) Pyrene. The results of PAH compound ratio individual analysis showed that polycyclic aromatic hydrocarbons compound at Jakarta Bay seawater came from oil spill and incomplete combustion mixture of organic material such as wood, grass, fuel oil, and fuel industry combustion activity.